Genome-wide association study and genotypic variation for the major tocopherol content in rice grain - Kazemzadeh, Sara; Farrokhi, Naser; Ahmadikhah, Asadollah; Tabar Heydar, Kourosh; Gilani, Abdolali; Askari, Hossein; Ingvarsson, Pär K. (Frontiers in Plant Science, 2024)
Rice tocopherols, vitamin E compounds with antioxidant activity, play essential roles in human health. Even though the key genes involved in vitamin E biosynthetic pathways have been identified in plants, the genetic architecture of vitamin E content in rice grain remains unclear. A genome-wide association study (GWAS) on 179 genotypically diverse rice accessions with 34,323 SNP markers was conducted to detect QTLs that define total and α-tocopherol contents in rice grains. Total and α-tocopherol contents had a strong positive correlation and varied greatly across the accessions, ranging from 0.230-31.76 and 0.011-30.83 (μg/g), respectively. A total of 13 QTLs were identified, which were spread across five of the rice chromosomes. Among the 13 QTLs, 11 were considered major with phenotypic variation explained (PVE) greater than 10%. Twelve transcription factor (TF) genes, one microprotein (miP), and a transposon were found to be associated with the QTLs with putative roles in controlling tocopherol contents. Moreover, intracellular transport proteins, ABC transporters, nonaspanins, and SNARE, were identified as associated genes on chromosomes 1 and 8. In the vicinity of seven QTLs, protein kinases were identified as key signaling factors. Haplotype analysis revealed the QTLs qAlph1. 1, qTot1.1, qAlph2.1, qAlph6.1, qTot6.1, and qTot8.3 to have significant haplogroups. Quantitative RT-PCR validated the expression direction and magnitude of WRKY39 (Os02g0265200), PIP5Ks (Os08g0450800), and MADS59 (Os06g0347700) in defining the major tocopherol contents. This study provides insights for ongoing biofortification efforts to breed and/or engineer vitamin E and antioxidant levels in rice and other cereals.